DIY Automated Feeding and Motion Recording System for the Analysis of Fish Behavior. (August 2019) - Pylatiuk, Christian; Zhao, Haiyu; Gursky, Eduard; Reischl, Markus; Peravali, Ravindra; Foulkes, Nicholas; Loosli, Felix
Fish species such as medaka or zebrafish are widely used as animal models to study physiology, disease development, and treatment efficacy. They are also used to study the rapidly growing field of behavior research, such as social interactions, anxiety, and the influence of environmental factors. Here we describe an automated experimental setup allowing the recording of general locomotor activity in combination with a food-on-demand system. It can simply be built with some basic electronic knowledge. Our setup enables the recording of locomotor and feeding activity of several fish for long-term studies, excluding disturbing external influences. A description of the automated recording system is given, as well as examples of recordings to illustrate its applicability for the study of fish behavior. The construction manual and operation instructions can be downloaded for free.